The effect of microwave disinfection in treating Candida-associated denture stomatitis and on the dimensional stability of denture base acrylic resins - Costa, Rodrigo Moreira Bringel da (2021)
Microwave disinfection has been reported as an alternative method for treating Candida-associated denture stomatitis (CADS). However, the information regarding the best protocol for treating Candida-associated denture stomatitis, and that does not promote changes on the dimensional stability of the complete dentures, is still scarce and diverging. Therefore, the objective of this study was to systematically assess the effectiveness of microwave disinfection against CADS (part 1), and its effect on the dimensional stability of denture base acrylic resins (part 2). The PubMed/MEDLINE, EMBASE, and SCOPUS databases were searched for randomized clinical trials (part 1), and clinical and in vitro studies (part 2) published in English, that have compared microwave disinfection to positive and/or control groups. The main outcomes were the improvement of the clinical signs and/or the decrease in the residual yeast of the dentures and palatal mucosa, and the changes on the dimensional stability measured in grams. Therefore, the mean differences, standard deviations, risk ratio, and 95% confidence interval were calculated by using the random-effects model. Heterogeneity was assessed by using Cochrans Q test and I2 values. The level of significance was set at p<.05. A total of 5 randomized clinical trials were included in the first part, and 7 in vitro studies in the second. The results demonstrated that microwave disinfection presented comparable effectiveness (p>0.05) to antifungal therapy with topical nystatin (100.000 IU/mL), chemical disinfection with 2% chlorhexidine and 0.02% sodium hypochlorite, and was more effective than topical application of miconazole (p<0.05). In addition, the results did not show significant differences, between microwave disinfection and topical nystatin (100.000 IU/mL) for the mycological counts, and cure and recurrence rates (p>0.05). Regarding the dimensional stability, microwave disinfection produced significant changes when compared with sodium hypochlorite, chloride solution, chlorhexidine, and water immersion (p<0.05). However, disinfecting dentures at 500 Watts for 3 minutes, and 450 Watts for 5 minutes, produced similar (p>0.05) and better (p<0.05) results in comparison with control groups. Thus, microwave disinfection showed comparable results to conventional treatments protocols used against CADS, with the protocol using 650 Watts for 3 minutes, once a week for 14 days, presenting the best cost-effectiveness for both prevention and treatment of CADS. In addition, microwave disinfection at 500 Watts for 3 minutes, and 450 Watts for 5 minutes, indicated to be safer for the dimensional stability of denture base acrylic resins